Polimorfismos no gene dupA de Helicobacter pylori e risco de úlcera duodenal e carcinoma gástrico - Rafaella Ferreira Avelar Costa (2011)
The dupA (“duodenal ulcer promoting gene A”) is constituted by two virB4 genes, jhp0917 and jhp0918, that forms one single gene of 1839 base pairs when there is an insertion of a T or C base after the position 1385 of the jhp0917 3’ region. The gene was described as a putative virulence marker of H. pylori associated exclusively with duodenal peptic ulcer in Asiatic patients. However, the study of this marker in strains isolated from different populations has showed wide variation in its association with diseases. In Brazil, the prevalence of strains considered to be dupA positive by PCR is too high and the presence of the gene has not been associated with the diseases associated with H. pylori infection. The differences observed in the literature may be due to the detection of only part of the gene, when conventional methods are used, since polymorphisms that create premature stop codon have been described. The aim of this study was to investigate, by gene sequencing, the presence of polymorphisms in the entire extension of the dupA gene from H. pylori strains isolated from patients with gastritis (n=26), duodenal ulcer (n=29) and gastric carcinoma (n=20), using the methodology of Primer Walking. From the 75 strains, 41 (54.7%) did not have polymorphisms that create stop codons before the 1839 position and were considered as dupA-intact. On the other hand, 34 (45.3%) strains had one or more polymorphisms that create premature stop codons, splitting the gene in smaller products than the one described as dupA. The presence of the intact dupA was more frequently observed in strains isolated from patients with duodenal ulcer [n=19 (65.5%)] than those from patients with gastritis [n=12 (46.2%)] or gastric carcinoma [n=10 (50%)]. In logistic analysis, adjusting for gender and age, the presence of intact dupA independently associated with duodenal ulcer (p=0.02, OR=5.06, IC 95%=1.22 – 20.96), indicating that the gene is a risk factor for the disease in our population.